A novel photoactive and three-dimensional stainless steel anode dramatically enhances the current density of bioelectrochemical systems. (April 2018) - Feng, Huajun; Tang, Chenyi; Wang, Qing; Liang, Yuxiang; Shen, Dongsheng; Guo, Kun; He, Qiaoqiao; Jayaprada, Thilini; Zhou, Yuyang; Chen, Ting; Ying, Xianbin; Wang, Meizhen
Abstract: This study reports a high-performance 3D stainless-steel photoanode (3D SS photoanode) for bioelectrochemical systems (BESs). The 3D SS photoanode consists of 3D carbon-coated SS felt bioactive side and a flat α-Fe2 O3 -coated SS plate photoactive side. Without light illumination, the electrode reached a current density of 26.2 ± 1.9 A m −2, which was already one of the highest current densities reported thus far. Under illumination, the current density of the electrode was further increased to 46.5 ± 2.9 A m −2 . The mechanism of the photo-enhanced current production can be attributed to the reduced charge-transfer resistance between electrode surface and the biofilm with illumination. It was also found that long-term light illumination can enhance the biofilm formation on the 3D SS photoanode. These findings demonstrate that using the synergistic effect of photocatalysis and microbial electrocatalysis is an efficient way to boost the current production of the existing high-performance 3D anodes for BESs. Graphical abstract: Image 1 Highlights: High current density (26.2 A m −2 ) was achieved on carbon-coating SS felt. Photocatalyst could further increase the current of carbon-SS felt to 46.5 A m −2 . Electron transfer between electrode/biofilm was accelerated by instant illumination. Biofilm morphology was optimized in the pressure of long-term illumination.